Students' Mathematical Problem-Solving Ability Based on Pedagogic Analysis of Mathematics Learning - Patunah, Siti; Herman, Tatang (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
Students' mathematical problem-solving skills are an important ability to have. One of the factors that can affect mathematical problem-solving ability is the teacher's pedagogic in learning mathematics. This study aims to analyze the pedagogical aspects of mathematics learning. The research method used is a qualitative approach with a descriptive method. The research subjects consisted of 35 grade VIII students in one of the schools in the city of Bandung. Data collection was carried out through observation of the mathematics learning process, test items of mathematical problem-solving skills, and the implementation of interviews with teachers and students. Data analysis was carried out by calculating the percentage of answers to the item test for mathematical problem-solving ability and analyzing the pedagogic learning of mathematics. The results showed that the average mathematical problem-solving ability as a whole reached 64.5%, indicating a medium category. The lowest indicator of mathematical problem-solving ability is the recheck indicator. Based on the analysis of pedagogic aspects in mathematics learning on mathematical problem-solving abilities related to teachers' ability to use learning methods and technology. This means that learning methods and technology are important in improving students' mathematical problem-solving skills.